Perancangan Job Mix Design untuk Uprating Kapasitas IPA Sunggal Menjadi 400 Liter Per Detik - Fahri, Tengku Muhammad; Ridha, Muhammad Abdhi; Hutasuhut, Syafrida Hanum (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to design an optimal Job Mix Design (JMD) in supporting the uprating construction work of the Sunggal Water Treatment Plant (IPA) up to a capacity of 400 liters per second. The research method uses a quantitative approach with the stages of data collection, material selection, concrete composition design, and quality testing. The materials used include type I cement from Semen Padang, sand and split stone from Sei Wampu Binjai, drilled well water, and Plastiment P121R additional materials. The results showed that the optimal composition for 1 m³ of concrete K-250 consisted of 305 kg of cement, 835 kg of sand, 388 kg of 10-20 mm split, 718 kg of 20-30 mm split, 150 liters of water, and 0.92 liters of P121R Plastiment. Tests show that concrete achieves a characteristic compressive strength of 250 kg/cm² at 28 days of age with a slump value of 12±2 cm. The use of local materials contributes to transportation cost efficiency and supports the local economy. The use of Plastiment P121R as an additive improves the workability of concrete and reduces the need for water in the mixture. This research results in a concrete design that meets the technical specifications for IPA uprating construction with an efficient and sustainable approach, and can be a model for the development of water treatment infrastructure in the future.